OCT guidance during stent implantation in primary PCI: A randomized multicenter study with nine months of optical coherence tomography follow-up. (1st January 2018) - Kala, Petr; Cervinka, Pavel; Jakl, Martin; Kanovsky, Jan; Kupec, Andrej; Spacek, Radim; Kvasnak, Martin; Poloczek, Martin; Cervinkova, Michaela; Bezerra, Hiram; Valenta, Zdenek; Attizzani, Guilherme F.; et al.
Abstract: Aims: To assess the possible merits of optical coherence tomography (OCT) guidance in primary percutaneous coronary intervention (pPCI). Methods and results: 201 patients with ST-elevation myocardial infarction (STEMI) were enrolled in this study. Patients were randomized either to pPCI alone (angio-guided group, n = 96) or to pPCI with OCT guidance (OCT-guided group, n = 105) and also either to biolimus A9 or to everolimus-eluting stent implantation. All patients were scheduled for nine months of follow-up angiography and OCT study. OCT guidance led to post-pPCI optimization in 29% of cases (59% malapposition and 41% dissections). No complications were found related to the OCT study. OCT analysis at nine months showed significantly less in-segment area of stenosis (6% [− 11, 19] versus 18% [3, 33]; p = 0.0002) in favor of the OCT-guided group. The rate major adverse cardiovascular events were comparable at nine months in both groups (3% in the OCT group versus 2% in the angio-guided group; p = 0.87). Conclusions: This study demonstrates the safety of OCT guidance during pPCI. The use of OCT optimized stent deployment in 1/3 of patients in this clinical scenario and significantly reduced in-segment area of stenosis at nine months of follow-up. Whether such improvements in OCT endpoints will have a positive impact on late clinical outcomes, they demand both a larger and longer-term follow-up study.